2019
DOI: 10.3390/ijms20246343
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Auxin Biosynthesis YUCCA Gene Family in Plants

Abstract: Auxin plays essential roles in plant normal growth and development. The auxin signaling pathway relies on the auxin gradient within tissues and cells, which is facilitated by both local auxin biosynthesis and polar auxin transport (PAT). The TRYPTOPHAN AMINOTRANSFERASE OF ARABIDOPSIS (TAA)/YUCCA (YUC) pathway is the most important and well-characterized pathway that plants deploy to produce auxin. YUCs function as flavin-containing monooxygenases (FMO) catalyzing the rate-limiting irreversible oxidative decarb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(131 citation statements)
references
References 164 publications
(293 reference statements)
0
88
0
Order By: Relevance
“…Specifically, all 10 remaining YUCCAs (YUC 2-11) from Arabidopsis have been characterized [52,55,[59][60][61][62][63], as well as other plant species, including the orthologue FLOOZY from petunia (Petunia X hybrida) [64] and fourteen orthologues from rice (OsYUCCA 1-14; Oryza sativa) [65,66]. YUCCA genes have also been characterized from tomato (Solanum lycopersicum) [67], maize (Zea mays) [68], potato (Solanum tuberosum) [69], strawberry (Fragaria vesca) [70] and cucumber (Cucumis sativus L.) [71] (see [72] for full list). To date, all characterized YUCCAs have been shown to be involved in auxin biosynthesis, catalyzing the oxidative decarboxylation reaction of IPA to form IAA.…”
Section: Yuccasmentioning
confidence: 99%
“…Specifically, all 10 remaining YUCCAs (YUC 2-11) from Arabidopsis have been characterized [52,55,[59][60][61][62][63], as well as other plant species, including the orthologue FLOOZY from petunia (Petunia X hybrida) [64] and fourteen orthologues from rice (OsYUCCA 1-14; Oryza sativa) [65,66]. YUCCA genes have also been characterized from tomato (Solanum lycopersicum) [67], maize (Zea mays) [68], potato (Solanum tuberosum) [69], strawberry (Fragaria vesca) [70] and cucumber (Cucumis sativus L.) [71] (see [72] for full list). To date, all characterized YUCCAs have been shown to be involved in auxin biosynthesis, catalyzing the oxidative decarboxylation reaction of IPA to form IAA.…”
Section: Yuccasmentioning
confidence: 99%
“…Plant hormone auxin is known to regulate various developmental and physiological processes (Cao et al, 2019). Among the genes whose expression is regulated by OsBBM1, we find members of the YUCCA family of auxin biosynthesis genes and some auxin response factors (Supplemental Data Set S1).…”
Section: Osbbm1 Upregulates Expression Of Auxin Biosynthesis Genesmentioning
confidence: 99%
“…YUCCA (YUC) genes encode flavin-containing monooxygenase enzymes that catalyze the rate-limiting step of oxidative decarboxylation of indole-3-pyruvate acid during auxin biosynthesis to form indole-3-acetic acid (IAA), the predominant auxin found in plants (Cao et al, 2019). The Arabidopsis genome encodes 11 YUCCA genes, whereas 14 members of this family have been identified in rice (Gallavotti et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies showed that YUCCA gene members shared highly conserved motifs, namely, the FAD-binding motif (GxGPxGLA), the nicotinamide adenine dinucleotide phosphate (NADPH)-binding motif (GxGxxGME), GC motif (ERxxxxASL), and ATG-containing motif (DxxxxATG) [24], which might be the pivotal sites for the biological functions of YUCCA genes. Furthermore, some evidence suggested that the FAD-and NADPH-binding motif GxGxxG is central to YUCCA activity [32].…”
Section: Introductionmentioning
confidence: 99%